Peran Guru dalam Mengembangkan Kemampuan Bertanya Siswa melalui Metode Problem Posing pada Mata Pelajaran SKI di MA Sumber Bungur Pakong Pamekasan - Mardhatillah, Mardhatillah; Arif, Saiful (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
This study aims to analyze the role of teachers in developing students’ questioning skills through the implementation of the problem posing method in Islamic Cultural History (SKI) learning, as well as to identify implementation challenges. This research employs a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation involving SKI teachers and class X-A students as primary informants, and analyzed through data reduction, data display, and conclusion drawing. The findings reveal that teachers act as facilitators, motivators, and evaluators in promoting active student engagement. The implementation of the problem posing method significantly improves students’ questioning skills, particularly in generating critical and reflective questions. However, challenges such as students’ low self-confidence and limited instructional time were identified. The novelty of this study lies in highlighting the strategic role of teachers in integrating the problem posing method to foster critical thinking through questioning activities in SKI learning. Therefore, this method offers an innovative alternative to enhance participatory and student-centered learning quality.